Histopathological findings in COVID-19 with concurrent septicaemia: an autopsy case report / Razuin Rahimi ... [et al.] - Rahim, Razuin (Faculty of Medicine, 2024)
COVID-19 infection results in a disease ranging from asymptomatic to severe pneumonia and death. This case report aimed to describe the autopsy findings of a COVID-19 positive patient with concurrent septicaemia associated with gastrointestinal tract perforation. We report a case of a 29-year-old prison detainee who collapsed and died at a hospital prior to a surgical procedure. The diagnosis of COVID-19 was confirmed by RT-PCR testing on postmortem nasopharyngeal swabs. Apart from fever, there was no COVID-19 symptoms reported by the patient. The autopsy revealed massive suppurative ascites with evidence of septicaemia and large bowel perforations. The lungs’ macroscopy did not show distinct pneumonic changes, however, microscopically, organizing pneumonia, perivascular lymphocytic infiltrates and increased number of megakyocytes were present. Vascular pathology such as endothelialitis and thrombosis were also seen in other organs. We affirmed the spectrum of pathological changes associated with COVID-19 infection from the previous studies. This case report highlighted that the detrimental microscopic changes could be present irrespective of the degree of severity of the clinical symptoms.